2021
DOI: 10.34188/bjaerv4n2-016
|View full text |Cite
|
Sign up to set email alerts
|

Análise espacial e temporal dos focos de calor no município de Anapu, Pará / Spatial and temporal analysis of fire focuses in the city of Anapu, Pará

Abstract: O presente artigo objetivou identificar os principais focos de queimadas no município de Anapu, Pará, nos anos de 2014 a 2019 e contribuir para a discussão sobre a avaliação espacial e temporal das queimadas em relação a existência de crimes ambientais no município. Para isso foram utilizadas ferramentas do sensoriamento remoto (SR) e sistema de informação geográfica (SIG) para o cruzamento e sobreposição dos dados utilizados nas análises. A base cartográfica do limite municipal foi obtido do Instituto Brasile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Access to clean air, for example, is necessary for the enjoyment of the right to health and the right to life [ 20 , 21 ]. Epidemiological studies have assessed and demonstrated the effects of air pollution on human health as potential factors in the occurrence of respiratory diseases, as well as an increase in the number of hospitalizations [ 22 , 23 , 24 , 25 , 26 ]. Herein, the research problem is that greater numbers of wildfires will contribute to an increase in hospitalizations due to respiratory diseases in children, young adolescents, and older people, because these are the most vulnerable age groups to atmospheric pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Access to clean air, for example, is necessary for the enjoyment of the right to health and the right to life [ 20 , 21 ]. Epidemiological studies have assessed and demonstrated the effects of air pollution on human health as potential factors in the occurrence of respiratory diseases, as well as an increase in the number of hospitalizations [ 22 , 23 , 24 , 25 , 26 ]. Herein, the research problem is that greater numbers of wildfires will contribute to an increase in hospitalizations due to respiratory diseases in children, young adolescents, and older people, because these are the most vulnerable age groups to atmospheric pollution.…”
Section: Introductionmentioning
confidence: 99%